Detection of Semi-volatile Plasticizers as a Signature of Early Electrical Fire - Han, Jia; Chen, Wenjia; Yu, Aihua; Yi, Jianxin (Frontiers in Materials, 2019)
Detection of characteristic species released from over-heated PVC cables may enable early warning of electrical fires. This work identified the major volatile species for over-heated PVC cables, and verified their potential as fire signatures with metal oxide gas sensors. Semi-volatile Dioctyl phthalate (DOP) and 2-Ethylhexanol (2-EH) were found to be ubiquitously present in the cable vapors as major species. Detection of these species and the vapors of overheated cables was accomplished with a metal oxide gas sensor. The response of the gas sensor to the cable vapors resulted mainly from DOP and 2-EH, demonstrating them as effective signature gases for over-heated PVC cables. A gas sensor based on SnO2 nanofibers was prepared with greatly enhanced response to the signature gases. Large-scale simulation tests showed that the nanofiber gas sensor could effectively detect the cable overheating at an early stage.